2022
DOI: 10.1002/smll.202205767
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering in 2D/2D Heterogeneous Photocatalysts

Abstract: reduction to energy-efficient fuels, [6][7][8] N 2 fixation to ammonia, [9] ammonia treatment, [10,11] and pollutants elimination. [12][13][14][15] Generally, photocatalysis is greatly affected by the composition, crystal structure, and electronic structure of photocatalysts. [16] Recently, 2D nanostructured photocatalysts have evoked interdisciplinary research interest because of their atomiclevel thickness, large specific surface area, excellent flexibility, unique physicochemical and electronic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 297 publications
0
21
0
Order By: Relevance
“…It is worth noting that stacking nonferroelectric materials can also produce unexpected ferroelectricity, which have been discovered in bilayer BN, bilayer TMDs, or h-BN/bilayer graphene/h-BN vdW heterostructure . The construction of heterogeneous structure can be obtained by growth, mechanical stacking or folding, , in which the ferroelectrity is strongly dependented on the stacking order, stacking direction, as well the layer number.…”
Section: Synthesis Of 2d Ferroicsmentioning
confidence: 99%
“…It is worth noting that stacking nonferroelectric materials can also produce unexpected ferroelectricity, which have been discovered in bilayer BN, bilayer TMDs, or h-BN/bilayer graphene/h-BN vdW heterostructure . The construction of heterogeneous structure can be obtained by growth, mechanical stacking or folding, , in which the ferroelectrity is strongly dependented on the stacking order, stacking direction, as well the layer number.…”
Section: Synthesis Of 2d Ferroicsmentioning
confidence: 99%
“…In recent years, the construction of 2D/2D heterostructure photocatalysts has been proven to effectively improve the photocatalytic activity . This is because the 2D/2D heterostructure can greatly increase the interface contact between the two; morphological engineering can facilitate the rapid migration and separation of photogenerated carriers, thus greatly reducing the recombination rate of photogenerated carriers and thereby improving the photocatalytic activity. , In view of this, herein, cotton fiber biochar (CFB) nanosheets were used to modify the BWO nanosheets by a simple hydrothermal process, and the CFB–BWO 2D/2D heterostructure photocatalysts were thus obtained.…”
Section: Introductionmentioning
confidence: 99%
“…20–24 It has been reported that 2D/2D hybrids possess a high charge separation rate due to the large interfacial contact area and short transfer distance, showing great promise in photocatalysis. 25–28 2D MXenes show unique thickness-dependent physicochemical features, a high specific surface area, and abundant active sites and can be regarded as ideal components to construct 2D/2D hybrids. 29,30 Moreover, the synergistic effect of photocatalysis and photothermal conversion can greatly improve the water purification efficiency, and MXene-based materials can be regarded as ideal substrates enabling the synergetic effect for water evaporation.…”
Section: Introductionmentioning
confidence: 99%